Copper-based catalyst for preparing CH4 by reducing CO2 through electro-catalysis and preparation and application of copper-based catalyst
By using semi-open pore silica nanosphere support and copper-based catalysts, the problems of low catalyst yield and low selectivity in electrocatalytic carbon dioxide reduction were solved, and efficient methane production was achieved, with a Faraday efficiency reaching 71.1%.
Patent Information
- Application Number
- CN202510038703.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-09
AI Technical Summary
In the existing electrocatalytic carbon dioxide reduction technology, the catalyst yield is low and the selectivity is low, resulting in limited reaction rate and excessive side reactions, which increases costs.
Silica nanospheres with semi-open pores are used as support to support the copper-based catalyst, and the activity and selectivity of the catalyst are improved by regulating the content of copper salt.
Extremely high methane selectivity and yield over a wide potential range, with a Faraday efficiency of 71.1%, significantly improving the performance of the catalyst.
Smart Images

Figure CN119824467A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts and relates to a copper-based catalyst, and in particular to a copper-based catalyst for preparing methane by electrocatalytic reduction of carbon dioxide and a preparation method and application thereof. Background Art
[0002] Electrocatalytic carbon dioxide reduction (CO2RR) methanogenesis technology is an important way to achieve the goal of carbon neutrality. This technology can convert CO2 into valuable chemicals and fuels (such as methane), which not only helps to reduce greenhouse gas emissions, but also provides solutions for the storage of renewable energy. To achieve the efficiency, stability and economy of this process, the selection of suitable catalysts is the key. At present, the catalysts that are studied more mainly include copper-based, gold-based, silver-based, zinc-based and other metals and their alloy materials, as well as some non-metallic materials such as carbon-based materials, nitrides, phosphides, etc. Among them, copper-based catalysts show high activity and selectivity, and are considered to be the most promising catalysts for the electroreduction of CO2 to methane.
[0003] In order to further improve the activity and stability of copper-based catalysts, researchers have designed and prepared catalysts through various means such as nano-sizing, forming alloys, constructing defects, and adjusting surface structures. For example, by constructing copper nanoparticles or copper alloy nanostructures, the catalytic active sites can be effectively increased and the catalytic efficiency can be improved. Despite this, the copper-based catalysts reported in the prior art still have the problems of low yield and low selectivity. This is because: first, the number of active sites on the catalyst surface is limited, especially at high current density, the lack of active sites will lead to limited reaction rate. Secondly, there are side reactions that compete for active sites and electrons in the CO2RR process. In addition to methane production, other by-products such as hydrogen, carbon monoxide, formic acid, etc. may be produced, thereby reducing the selectivity of methane production. This also means that practical applications often require higher power consumption to drive the reaction, resulting in a significant increase in cost.
[0004] In addition, the catalyst carrier commonly used in the current electrocatalytic carbon dioxide reduction technology is a carbon-based material (activated carbon, carbon nanotubes, etc.), a metal oxide, a conductive polymer, etc. One of the common points of these catalyst carriers is to have good electrical conductivity. This is because, as known to those skilled in the art, if the carrier does not have electrical conductivity, there will be situations such as low current density and excessive side reactions in the catalytic process, thereby causing the reduction of catalytic activity and selectivity, further increasing the cost. Silica nanosphere is a porous silica material, with the characteristics of small particle size, large specific surface area, porous structure, high chemical stability, and has been widely used in the fields of separation, drug release, analysis and detection. But silicon dioxide does not have electrical conductivity, as mentioned above, if it is used as a carrier of a catalyst, there may be situations such as low current density and excessive side reactions in the electrocatalytic process.
[0005] At present, in the field of electrocatalytic carbon dioxide reduction, there are no reports on catalysts using silica nanospheres as carriers. Summary of the invention
[0006] In view of the problems of low catalyst yield and low selectivity in the electrocatalytic reduction of carbon dioxide to prepare methane in the prior art, the present invention provides a method for preparing a copper-based catalyst for electrocatalytic reduction of carbon dioxide to prepare methane. The copper-based catalyst uses silica nanospheres with semi-open pores as a carrier, has good performance in electrocatalytic reduction of CO2 to CH4, not only shows extremely high CH4 selectivity in a wide potential range, but also significantly improves the yield, achieving unexpected technical effects. In addition, the preparation method of the copper-based catalyst is simple and easy to operate, and has the prospect of industrial application.
[0007] The technical solution of the present invention:
[0008] A method for preparing a copper-based catalyst supported by silicon dioxide nanospheres comprises the following steps:
[0009] (1) Preparation of silica nanospheres: Add appropriate amounts of water, butyraldehyde and CTAB to a closed reaction device and stir under alkaline conditions until the mixture is uniformly mixed. Then add an appropriate amount of TEOS and react at room temperature under stirring for 20-28 hours. Liquid-solid separation, wash, dry and calcine the obtained white solid to obtain a yellow solid - silica nanospheres with a semi-open pore morphology, i.e., MSN carrier. This step uses a certain concentration of CTAB aqueous solution in an alkaline solution to achieve the regulation of the growth of silica nanospheres, and finally forms a semi-open pore morphology with a tree-like morphology, thereby obtaining an MSN carrier for preparing a copper-based catalyst. This application pioneered the use of non-conductive silica nanospheres as catalyst carriers for electrocatalytic carbon dioxide reduction technology, overcoming technical prejudice.
[0010] Wherein, the mass ratio of water, butyraldehyde, CTAB and TEOS is 100-140:104-136:5-8:20-22. The alkaline condition is: pH=11-12. The washing is specifically: washing with water or ethanol for 3-5 times. The drying is specifically: drying at 70-90°C for 12-18 hours. The calcination is specifically: heating to 500-550°C at a heating rate of 10°C / min and calcining for 5-7h. Compared with ordinary nanospheres, the MSN prepared in this application is a mesoporous SiO2 carrier with a more excellent pore structure, which not only provides more abundant Si-OH, which is conducive to the binding of Cu, and then forms more catalytic sites for subsequent electrocatalytic reduction reactions, but also is more conducive to the diffusion of CO2 molecules compared with the physical structure of ordinary nanospheres.
[0011] (2) Loading of copper-based catalyst: Take an appropriate amount of the MSN carrier prepared in step (1) and divalent copper salt in water and stir until the copper salt is dissolved and evenly dispersed. Then add urea and stir the reaction at 60-100°C and alkaline conditions for 3-5 hours. Liquid-solid separation, wash, dry and calcine the obtained blue solid to obtain a blue-green powder, i.e., silica nanosphere-loaded copper-based catalyst Cu-MSN-I. In this step, according to the chemical precipitation of cations, the copper salt is precipitated on the MSN surface in a highly dispersed form to obtain a silica nanosphere-loaded copper electrocatalyst Cu-MSN-I with semi-open pores.
[0012] Among them, the amount of divalent copper salt is 1.4-1.6mmol copper salt / gMSN carrier, and the amount of urea is 11-13mmol urea / gMSN carrier; the alkaline condition is: pH=10-11. The washing is specifically: washing with water 3-5 times. The drying is specifically: drying at 50-70℃ for 12-18 hours. The calcination is specifically: heating to 300-350℃ at a heating rate of 10℃ / min, and calcining for 4h-6h. The inventor unexpectedly found that only at a specific content can copper salt be fixed on the surface of the MSN carrier in a fine and highly dispersed form; thereby further making the prepared copper-based catalyst have a more significant methane catalytic effect than ordinary catalysts (FE>70%, CH4 Faraday efficiency of 71.1%). In addition, too high or too low a content of copper salt during the loading process will cause a sudden change in morphology and fail to achieve the expected results.
[0013] Preferably, the divalent copper salt is copper chloride, copper nitrate or copper sulfate.
[0014] The catalyst Cu-MSN-I prepared by the above method, the copper-based catalyst Cu-MSN-I, produced unexpected technical effects in the electrocatalytic CO2 reduction reaction to produce methane. The inventor speculated through research that this is because the composite catalyst formed by combining silica nanospheres with copper metal, under a specific loading amount, provides an electron conduction path through the conductive material, and the silica nanospheres provide structural support and specific catalytic active sites, achieving a synergistic effect between the two, thereby showing excellent selectivity and yield.
[0015] The catalyst Cu-MSN-I is used in electrocatalytic CO2 reduction to produce CH4.
[0016] The present application also provides another catalyst. The inventors have found in their research that when the amount of the divalent copper salt in step (1) is 7-8 mmol copper salt / g MSN carrier, a silica nanosphere-supported copper-based catalyst Cu-MSN-II is obtained.
[0017] The catalyst Cu-MSN-II prepared by the above method is different from the copper-based catalyst Cu-MSN-I in that the product of the electrocatalytic CO2 reduction reaction using the copper-based catalyst Cu-MSN-II is ethylene.
[0018] The catalyst Cu-MSN-II as described above is used in the electrocatalytic reduction of CO2 to produce C2H4.
[0019] Beneficial effects of the present invention:
[0020] (1) The copper-based catalyst loaded with silica nanospheres described in the present invention exhibits extremely high selectivity (FE of CH4>60%) and yield (CH4 Faraday efficiency reaches 71.1%) in the electrocatalytic reduction of carbon dioxide to produce methane, which solves the problems of low catalyst yield and low selectivity in the prior art and represents a significant improvement.
[0021] (2) The silica nanosphere-loaded copper-based catalyst described in the present invention innovatively uses non-conductive silica nanospheres as a carrier and exhibits excellent performance at a certain copper salt content, producing unexpected technical effects.
[0022] (3) The present invention provides a method for preparing the silica nanosphere-loaded copper-based catalyst. The preparation method has simple steps and mild conditions. Since it is simpler than other catalyst synthesis processes, it has important significance for practical applications.
[0023] (4) The preparation method described in the present application can freely realize the regulation of the electrocatalytic carbon dioxide reduction product - methane or ethylene by regulating the content of copper salt loaded in the MSN carrier, which can meet different needs and has broader application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope image of the copper-based catalyst Cu-MSN-I prepared in Example 2 of the present invention.
[0025] Figure 2 This is a transmission electron microscope image of the copper-based catalyst Cu-MSN-I prepared in Example 2 of the present invention.
[0026] Figure 3 This is a scanning electron microscope image of the copper-based catalyst Cu-MSN-II prepared in Example 5 of the present invention.
[0027] Figure 4 This is a transmission electron microscope image of the copper-based catalyst Cu-MSN-II prepared in Example 5 of the present invention.
[0028] Figure 5This is an energy dispersive X-ray spectrum of the copper-based catalyst Cu-MSN-I prepared in Example 2 of the present invention.
[0029] Figure 6 This is an energy dispersive X-ray spectrum of the copper-based catalyst Cu-MSN-II prepared in Example 5 of the present invention.
[0030] Figure 7 X-ray powder diffraction patterns of the copper-based catalyst Cu-MSN-I prepared in Example 2 and the copper-based catalyst Cu-MSN-II prepared in Example 5 of the present invention.
[0031] Figure 8 These are the N2 adsorption-desorption isotherms of the copper-based catalyst Cu-MSN-I prepared in Example 2 of the present invention and the copper-based catalyst Cu-MSN-II prepared in Example 5.
[0032] Fig. 9 The pore size distribution diagrams of the copper-based catalyst Cu-MSN-I prepared in Example 2 and the copper-based catalyst Cu-MSN-II prepared in Example 5 of the present invention.
[0033] Fig.10 This is the Faraday efficiency diagram of the copper-based catalyst Cu-MSN-I electrocatalytic CO2 reduction prepared in Example 2 of the present invention.
[0034] Fig.11 This is the Faraday efficiency diagram of the copper-based catalyst Cu-MSN-II electrocatalytic CO2 reduction prepared in Example 5 of the present invention.
[0035] Fig.12 This is the in-situ infrared spectrum of the copper-based catalyst Cu-MSN-I prepared in Example 2 of the present invention for electrocatalytic CO2 reduction.
[0036] Fig.13 This is the in-situ infrared spectrum of the copper-based catalyst Cu-MSN-II electrocatalytic CO2 reduction prepared in Example 5 of the present invention.
[0037] Fig.14 This is a scanning electron microscope image of the smooth-surfaced spherical nanosphere-loaded copper catalyst prepared in Comparative Example 2.
[0038] FIG. 15 is a diagram showing the Faraday efficiency of electrocatalytic CO2 reduction using a copper catalyst loaded on smooth-surface spherical nanospheres prepared in Comparative Example 1-2.
[0039] FIG. 16 is a diagram showing the Faraday efficiency of electrocatalytic CO2 reduction of Cu-MSN catalysts with different Cu loadings prepared in Comparative Examples 3-5. DETAILED DESCRIPTION
[0040] The present invention will be further described below in conjunction with the embodiments.
[0041] The raw materials used in this application, unless otherwise specified, were purchased from commercial sources. Among them, copper nitrate (Cu(NO3)2·3H2O, 99%), tetraethyl orthosilicate (TEOS,>99%), urea (99.5%), ammonia water (NH4OH, 25-28%), and hexadecyltrimethylammonium bromide (CTAB) were purchased from China National Pharmaceutical Chemical Reagent Co., Ltd. Butyraldehyde (C4H8O, 99%) was purchased from Shanghai McLean Biochemical Co., Ltd. Copper chloride, copper nitrate, and copper sulfate were purchased from China National Pharmaceutical Chemical Reagent Co., Ltd. All materials were used directly without further purification. Deionized water was used in all synthetic processes.
[0042] Example 1: Preparation of Silica Nanosphere-supported Copper-based Catalyst Cu-MSN-I
[0043] (1) Preparation of silica nanospheres: 10 g of water, 10.4 g of butyraldehyde and 0.5 g of CTAB were added to a closed reaction device and stirred under alkaline conditions until the mixture was uniformly mixed. Then 2 g of TEOS was added and the mixture was stirred at room temperature for 20 h. After liquid-solid separation, the obtained white solid was washed, dried and calcined to obtain a yellow solid - silica nanospheres with semi-open pores, i.e., MSN carriers.
[0044] The alkaline condition is: pH = 11 (adding an appropriate amount of NH4OH). The washing is specifically: washing with ethanol for 3 times. The drying is specifically: drying at 70°C for 18 hours. The calcination is specifically: heating to 500°C at a heating rate of 10°C / min and calcining for 7 hours.
[0045] (2) Loading of copper-based catalyst: 0.35 g of the MSN carrier prepared in step (1) and an appropriate amount of copper chloride were added to water and stirred until the copper salt was dissolved and evenly dispersed. Urea was then added and stirred for 5 h at 60° C. under alkaline conditions. Liquid-solid separation was performed, and the obtained blue solid was washed, dried, and calcined to obtain a blue-green powder, i.e., the silica nanosphere-loaded copper-based catalyst Cu-MSN-I.
[0046] The amount of copper chloride used is 1.4 mmol copper salt / gMSN carrier, and the amount of urea used is 11 mmol urea / gMSN carrier; the alkaline condition is: pH = 10. The washing is specifically: washing with water 3 times. The drying is specifically: drying at 50°C for 18 hours. The calcination is specifically: heating to 300°C at a heating rate of 10°C / min and calcining for 6 hours.
[0047] Example 2: Preparation of Silica Nanosphere-supported Copper-based Catalyst Cu-MSN-I
[0048] Different from Example 1, (1) Preparation of silica nanospheres: 12 g of water, 12 g of butyraldehyde and 0.64 g of CTAB were added to a closed reaction device and stirred under alkaline conditions until they were uniformly mixed. Then 2.1 g of TEOS was added and reacted at room temperature for 24 h under stirring. Liquid-solid separation was performed, and the obtained white solid was washed, dried and calcined to obtain a yellow solid - silica nanospheres with semi-open pore morphology, i.e., MSN carriers.
[0049] The alkaline condition is: pH = 11. The washing is specifically: washing with ethanol for 4 times. The drying is specifically: drying at 75°C for 14 hours. The calcination is specifically: heating to 510°C at a heating rate of 10°C / min and calcining for 5.5 hours.
[0050] (2) Loading of copper-based catalyst: 0.35 g of the MSN carrier prepared in step (1) and an appropriate amount of copper nitrate were added to water and stirred until the copper salt was dissolved and evenly dispersed. Urea was then added and stirred for 3.5 h at 70° C. under alkaline conditions. Liquid-solid separation was performed, and the obtained blue solid was washed, dried, and calcined to obtain a blue-green powder, i.e., the silica nanosphere-loaded copper-based catalyst Cu-MSN-I.
[0051] The amount of copper nitrate used is 1.5 mmol copper salt / gMSN carrier, and the amount of urea used is 11.5 mmol urea / gMSN carrier; the alkaline condition is: pH = 10. The washing is specifically: washing with water 4 times. The drying is specifically: drying at 55°C for 14 hours. The calcination is specifically: heating to 320°C at a heating rate of 10°C / min and calcining for 4.5 hours.
[0052] Example 3: Preparation of Silica Nanosphere-supported Copper-based Catalyst Cu-MSN-I
[0053] Different from Example 1, (1) Preparation of silica nanospheres: 13 g of water, 12.6 g of butyraldehyde and 0.7 g of CTAB were added to a closed reaction device and stirred under alkaline conditions until uniformly mixed. Then 2.15 g of TEOS was added and reacted at room temperature for 26 h under stirring. Liquid-solid separation was performed, and the obtained white solid was washed, dried and calcined to obtain a yellow solid - silica nanospheres with semi-open pore morphology, i.e., MSN carriers.
[0054] The alkaline condition is: pH = 12. The washing is specifically: washing with ethanol for 4 times. The drying is specifically: drying at 80°C for 16 hours. The calcination is specifically: heating to 530°C at a heating rate of 10°C / min and calcining for 6 hours.
[0055] (2) Loading of copper-based catalyst: 0.35 g of the MSN carrier prepared in step (1) and an appropriate amount of copper sulfate were added to water and stirred until the copper salt was dissolved and evenly dispersed. Urea was then added and stirred for 4 h at 80°C under alkaline conditions. Liquid-solid separation was performed, and the obtained blue solid was washed, dried, and calcined to obtain a blue-green powder, i.e., the silica nanosphere-loaded copper-based catalyst Cu-MSN-I.
[0056] The amount of copper sulfate used is 1.5 mmol copper salt / gMSN carrier, and the amount of urea used is 12 mmol urea / gMSN carrier; the alkaline condition is: pH = 11. The washing is specifically: washing with water 4 times. The drying is specifically: drying at 65°C for 16 hours. The calcination is specifically: heating to 340°C at a heating rate of 10°C / min and calcining for 5 hours.
[0057] Example 4: Preparation of Silica Nanosphere-supported Copper-based Catalyst Cu-MSN-I
[0058] (1) Preparation of silica nanospheres: 14 g of water, 13.6 g of butyraldehyde and 0.8 g of CTAB were added to a closed reaction device and stirred under alkaline conditions until the mixture was uniformly mixed. Then 2.2 g of TEOS was added and the mixture was stirred at room temperature for 20-28 h. Liquid-solid separation was performed, and the obtained white solid was washed, dried and calcined to obtain a yellow solid - silica nanospheres with semi-open pores, i.e., MSN carriers.
[0059] The alkaline condition is: pH = 12 (adding an appropriate amount of NH4OH). The washing is specifically: washing with ethanol for 5 times. The drying is specifically: drying at 90°C for 12 hours. The calcination is specifically: heating to 550°C at a heating rate of 10°C / min and calcining for 5 hours.
[0060] (2) Loading of copper-based catalyst: 0.35 g of the MSN carrier prepared in step (1) and an appropriate amount of copper nitrate were added to water and stirred until the copper salt was dissolved and evenly dispersed. Urea was then added and stirred for 3 h at 100 ° C under alkaline conditions. Liquid-solid separation was performed, and the obtained blue solid was washed, dried, and calcined to obtain a blue-green powder, i.e., the silica nanosphere-loaded copper-based catalyst Cu-MSN-I.
[0061] The amount of copper nitrate used is 1.6 mmol copper salt / gMSN carrier, and the amount of urea used is 13 mmol urea / gMSN carrier; the alkaline condition is: pH = 11. The washing is specifically: washing with water 5 times. The drying is specifically: drying at 70°C for 12 hours. The calcination is specifically: heating to 350°C at a heating rate of 10°C / min and calcining for 4 hours.
[0062] Example 5: Preparation of Silica Nanosphere-supported Copper-based Catalyst Cu-MSN-II
[0063] (1) Preparation of silica nanospheres: 10 g of water, 10.4 g of butyraldehyde and 0.5 g of CTAB were added to a closed reaction device and stirred under alkaline conditions until the mixture was uniformly mixed. Then 2 g of TEOS was added and the mixture was stirred at room temperature for 20 h. After liquid-solid separation, the obtained white solid was washed, dried and calcined to obtain a yellow solid - silica nanospheres with semi-open pores, i.e., MSN carriers.
[0064] The alkaline condition is: pH = 11. The washing is specifically: washing with ethanol for 3 times. The drying is specifically: drying at 70°C for 18 hours. The calcination is specifically: heating to 500°C at a heating rate of 10°C / min and calcining for 7 hours.
[0065] (2) Loading of copper-based catalyst: 0.35 g of the MSN carrier prepared in step (1) and an appropriate amount of copper chloride were added to water and stirred until the copper salt was dissolved and evenly dispersed. Urea was then added and stirred for 5 h at 60° C. under alkaline conditions. Liquid-solid separation was performed, and the obtained blue solid was washed, dried, and calcined to obtain a blue-green powder, i.e., the silica nanosphere-loaded copper-based catalyst Cu-MSN-I.
[0066] The amount of copper chloride used is 7 mmol copper salt / gMSN carrier, and the amount of urea used is 11 mmol urea / gMSN carrier; the alkaline condition is: pH = 10. The washing is specifically: washing with water 3 times. The drying is specifically: drying at 50°C for 18 hours. The calcination is specifically: heating to 300°C at a heating rate of 10°C / min and calcining for 6 hours.
[0067] Example 6: Preparation of Silica Nanosphere-supported Copper-based Catalyst Cu-MSN-II
[0068] Different from Example 4, (1) Preparation of silica nanospheres: 11.5 g of water, 11.5 g of butyraldehyde and 0.6 g of CTAB were added to a closed reaction device and stirred under alkaline conditions until uniformly mixed. Then 2.05 g of TEOS was added and reacted at room temperature for 24 h under stirring. Liquid-solid separation was performed, and the obtained white solid was washed, dried and calcined to obtain a yellow solid - silica nanospheres with semi-open pore morphology, i.e., MSN carriers.
[0069] The alkaline condition is: pH = 11. The washing is specifically: washing with ethanol for 4 times. The drying is specifically: drying at 80°C for 15 hours. The calcination is specifically: heating to 520°C at a heating rate of 10°C / min and calcining for 6 hours.
[0070] (2) Loading of copper-based catalyst: 0.35 g of the MSN carrier prepared in step (1) and an appropriate amount of copper nitrate were added to water and stirred until the copper salt was dissolved and evenly dispersed. Urea was then added and stirred for 3-5 h at 60-100° C. under alkaline conditions. Liquid-solid separation was performed, and the obtained blue solid was washed, dried, and calcined to obtain a blue-green powder, i.e., the silica nanosphere-loaded copper-based catalyst Cu-MSN-I.
[0071] The amount of copper nitrate used is 7.2 mmol copper salt / gMSN carrier, and the amount of urea used is 11.5 mmol urea / gMSN carrier; the alkaline condition is: pH = 10. The washing is specifically: washing with water 4 times. The drying is specifically: drying at 60°C for 13 hours. The calcination is specifically: heating to 330°C at a heating rate of 10°C / min and calcining for 5 hours.
[0072] Example 7: Preparation of Silica Nanosphere-supported Copper-based Catalyst Cu-MSN-II
[0073] Different from Example 4, (1) Preparation of silica nanospheres: 12.5 g of water, 13 g of butyraldehyde and 0.72 g of CTAB were added to a closed reaction device and stirred under alkaline conditions until uniformly mixed. Then 2.11 g of TEOS was added and reacted at room temperature for 26 h under stirring. Liquid-solid separation was performed, and the obtained white solid was washed, dried and calcined to obtain a yellow solid - silica nanospheres with semi-open pore morphology, i.e., MSN carriers.
[0074] The alkaline condition is: pH = 12. The washing is specifically: washing with ethanol for 4 times. The drying is specifically: drying at 85°C for 17 hours. The calcination is specifically: heating to 540°C at a heating rate of 10°C / min and calcining for 6.5 hours.
[0075] (2) Loading of copper-based catalyst: 0.35 g of the MSN carrier prepared in step (1) and an appropriate amount of copper sulfate were added to water and stirred until the copper salt was dissolved and evenly dispersed. Urea was then added and stirred for 4.5 h at 80° C. under alkaline conditions. Liquid-solid separation was performed, and the obtained blue solid was washed, dried, and calcined to obtain a blue-green powder, i.e., the silica nanosphere-loaded copper-based catalyst Cu-MSN-I.
[0076] The amount of copper sulfate used is 7.6 mmol copper salt / gMSN carrier, and the amount of urea used is 12.3 mmol urea / gMSN carrier; the alkaline condition is: pH = 11. The washing is specifically: washing with water 4 times. The drying is specifically: drying at 65°C for 15 hours. The calcination is specifically: heating to 340°C at a heating rate of 10°C / min and calcining for 5.5 hours.
[0077] Example 8: Preparation of Silica Nanosphere-supported Copper-based Catalyst Cu-MSN-II
[0078] Different from Example 4, (1) Preparation of silica nanospheres: 14 g of water, 13.6 g of butyraldehyde and 0.8 g of CTAB were added to a closed reaction device and stirred under alkaline conditions until uniformly mixed. Then 2.2 g of TEOS was added and reacted at room temperature for 28 h under stirring. Liquid-solid separation was performed, and the obtained white solid was washed, dried and calcined to obtain a yellow solid - silica nanospheres with semi-open pore morphology, i.e., MSN carriers.
[0079] The alkaline condition is: pH = 12. The washing is specifically: washing with ethanol for 5 times. The drying is specifically: drying at 90°C for 12 hours. The calcination is specifically: heating to 550°C at a heating rate of 10°C / min and calcining for 5 hours.
[0080] (2) Loading of copper-based catalyst: 0.35 g of the MSN carrier prepared in step (1) and an appropriate amount of copper nitrate were added to water and stirred until the copper salt was dissolved and evenly dispersed. Urea was then added and stirred for 3 h at 100 ° C under alkaline conditions. Liquid-solid separation was performed, and the obtained blue solid was washed, dried, and calcined to obtain a blue-green powder, i.e., the silica nanosphere-loaded copper-based catalyst Cu-MSN-I.
[0081] The amount of copper nitrate used is 8 mmol copper salt / gMSN carrier, and the amount of urea used is 13 mmol urea / gMSN carrier; the alkaline condition is: pH = 11. The washing is specifically: washing with water 5 times. The drying is specifically: drying at 70°C for 12 hours. The calcination is specifically: heating to 350°C at a heating rate of 10°C / min and calcining for 4 hours.
[0082] Comparative Example 1: Smooth-surface spherical nanospheres SSN as carrier (compared with Cu-MSN-I).
[0083] Different from Example 1, self-prepared spherical silicon nanospheres are used as the carrier of the copper-based catalyst.
[0084] Preparation method: Spherical silicon nanospheres were prepared by sol-gel method. The specific operation is: 25.5g deionized water and 11.8g ethanol were thoroughly stirred at 800 rpm in a round-bottom flask for 15 minutes. 0.08g CTAB, 0.5g TEOS and 0.55g ammonia water were added and stirred for 180 minutes. The whole experiment was carried out at room temperature. The obtained white product was washed with deionized water and ethanol 5 times and placed in an 80°C oven overnight. Then calcination was carried out, specifically: first calcined at 200°C for 2h, and then calcined at 600°C at a heating rate of 10°C / min for 4h to obtain the final product, smooth surface spherical nanospheres SSN.
[0085] Comparative Example 2: Smooth-surface spherical nanospheres as carriers (compared with Cu-MSN-II).
[0086] Different from Example 4, the smooth-surface spherical nanospheres SSN prepared in Comparative Example 1 were used as the carrier of the copper-based catalyst.
[0087] Comparative Example 3: Low copper-based catalyst loading
[0088] The difference from Example 1 is that the amount of copper nitrate used in step (2) is 0.3 mmol copper salt / g MSN carrier.
[0089] Comparative Example 4: Medium copper-based catalyst loading
[0090] The difference from Example 1 is that the amount of copper nitrate used in step (2) is 4.4 mmol copper salt / g MSN carrier.
[0091] Comparative Example 5: High copper-based catalyst loading
[0092] The difference from Example 1 is that the amount of copper nitrate used in step (2) is 10.5 mmol copper salt / g MSN carrier.
[0093] Example 9: Structural Characterization of Copper-Based Catalysts
[0094] The copper-based catalysts Cu-MSN-I prepared in Examples 1-4 and Cu-MSN-II prepared in Examples 5-8 were structurally characterized. Since the results are similar, the copper-based catalysts Cu-MSN-I prepared in Example 2 and the copper-based catalysts Cu-MSN-II prepared in Example 5 are used as examples for description. At the same time, the samples prepared in Comparative Examples 1-2 were subjected to scanning electron microscopy, and the results were consistent, and the samples prepared in Comparative Example 2 were used as an example for description.
[0095] (1) Scanning electron microscope detection
[0096] The copper-based catalyst Cu-MSN-I prepared in Example 2 was examined using a scanning electron microscope. Figure 1 As shown in FIG. 1 , the semi-open pore structure on the surface of MSN can be clearly seen. The copper-based catalyst Cu-MSN-I prepared in Example 5 was detected by scanning electron microscopy. Figure 3 As shown in Figure 2, it can be seen that the semi-open pore structure is almost occupied by Cu species. Figure 1 and Figure 3 It can be seen that the copper-based catalysts Cu-MSN-I and Cu-MSN-II prepared in the present application both have clearly visible semi-open channels. This is because the carriers used in both are MSNs with semi-open channels.
[0097] Fig.14 This is a scanning electron microscope image of the smooth surface spherical nanospheres loaded with copper catalyst prepared in Comparative Example 2. Fig.14 It can be seen that the SSN carrier is a spherical shape with a smooth surface, and the Cu species is successfully loaded on the surface of the silicon sphere.
[0098] (2) Transmission electron microscopy
[0099] The copper-based catalyst Cu-MSN-I prepared in Example 2 was examined using a transmission electron microscope. Figure 2 As shown in FIG. 1 , the semi-open pore structure on the surface of MSN can be clearly seen. The copper-based catalyst Cu-MSN-II prepared in Example 5 was detected by transmission electron microscopy. Figure 4 As shown in Figure 2, it can be seen that the semi-open pore structure is almost occupied by Cu species. Figure 2 and Figure 4 It can be seen that the copper-based catalysts Cu-MSN-I and Cu-MSN-II prepared in this application both have clearly visible semi-open channels, which is consistent with the results of scanning electron microscopy. However, in the copper-based catalyst Cu-MSN-II, due to the increase in the copper-based loading, the amount of catalytic additive in the channel structure also increases.
[0100] (3) Energy dispersive X-ray spectroscopy test
[0101] The copper-based catalyst Cu-MSN-I prepared in Example 2 was tested using energy dispersive X-ray spectroscopy. Figure 5 The copper-based catalyst Cu-MSN-II prepared in Example 5 was tested using energy dispersive X-ray spectroscopy. Figure 6 As shown. Figure 5 It can be observed that there are very weak characteristic signals of Cu element on the surface of Cu-MSN-I, indicating that Cu species are fixed on the surface and in the pores of silica nanospheres in a highly dispersed form. This result was unforeseen before the synthesis of the catalyst. Figure 6 It can be observed that there is a strong characteristic signal of Cu element on the surface of Cu-MSN-II, and Cu species fill the pores of silica nanospheres in the form of aggregation. This is because the concentration of copper nitrate solution is different during the synthesis process, resulting in different aggregation forms of Cu loaded on the carrier.
[0102] (4) X-ray powder diffractometer detection
[0103] The copper-based catalyst Cu-MSN-I prepared in Example 2 and the Cu-MSN-II prepared in Example 5 were tested by X-ray powder diffractometer. Figure 7 As shown. Figure 7 It can be seen that there are no obvious peaks in the XRD spectrum, indicating that the copper-based catalysts Cu-MSN-I and Cu-MSN-II are mainly amorphous phase structures.
[0104] (5) Physical adsorbent test
[0105] Physical adsorbent tests were performed on the copper-based catalyst Cu-MSN-I prepared in Example 2 and the copper-based catalyst Cu-MSN-II prepared in Example 5 to obtain the N2 adsorption and desorption isotherms of the catalysts ( Figure 8 ) and pore size distribution diagram ( Fig. 9 ).Depend on Figure 8 It can be seen that, unlike the copper-based catalyst Cu-MSN-II, the copper-based catalyst Cu-MSN-I exhibits an obvious H3-type hysteresis loop, which indicates that it retains the mesoporous structure of MSN. Fig. 9 It can be seen that the proportion of micropores in the copper-based catalyst Cu-MSN-I is relatively small, and there are more medium and large pores above 10nm; the proportion of micropores in the copper-based catalyst Cu-MSN-II has increased sharply, and the number of mesopores below 10nm has also increased. From this, it can be seen that: (a) the copper-based catalyst Cu-MSN-I retains the mesoporous structure of MSN; (b) small micropores appear in the aggregated Cu species in the copper-based catalyst Cu-MSN-II.
[0106] Example 10: Electrocatalytic chemical CO2 reduction test
[0107] Electrocatalytic chemical CO2 reduction tests were performed on the copper-based catalysts Cu-MSN-I prepared in Examples 1-4, the copper-based catalysts Cu-MSN-II prepared in Examples 5-8, and the silica nanosphere-loaded copper-based catalysts prepared in Control Examples 1-5.
[0108] (1) Electrochemical experiments
[0109] Test method: The electrochemical experiment was conducted using a Gamry 1010E electrochemical workstation and an H-type cell (the proton exchange membrane used was Nafion 117). + (saturated solution is KCl) and platinum sheet as working electrode, reference electrode and counter electrode respectively. CO2 reduction at different potentials was also carried out in CO2 saturated KHCO3 solution with a concentration of 0.1M. The test process requires a continuous flow of 100% CO2 gas flow with a flow rate of 30ml / min. 25ml 0.1M KHCO3 solution was perfused into the positive and negative electrodes of the electrolytic cell respectively. Gas phase products were detected by gas chromatograph (GC, Huifen 7820).
[0110] Test results: The copper-based catalyst Cu-MSN-I prepared in Example 2 and the copper-based catalyst Cu-MSN-II prepared in Example 5 are used as examples for illustration.
[0111] Fig.10 This is the Faraday efficiency diagram of the electrocatalytic CO2 reduction of the copper-based catalyst Cu-MSN-I prepared in Example 2 of the present invention. Fig.10 As shown, it can be seen that the copper-based catalyst Cu-MSN-I has the advantage of good electrocatalytic reduction of CO2 to CH4, showing extremely high CH4 selectivity (FE>60%) in a wide potential range, and the highest CH4 Faradaic efficiency reaches 71.1%. The Faradaic efficiency of the byproducts H2 and CO is extremely low, with the optimal potential of H2<10% and CO<2%.
[0112] Fig.11 This is the Faraday efficiency diagram of the copper-based catalyst Cu-MSN-II electrocatalytic CO2 reduction prepared in Example 5. Fig.11 As shown, it can be seen that the copper-based catalyst Cu-MSN-II has a good advantage in electrocatalytic reduction of CO2 to C2H4, showing extremely high C2H4 selectivity (FE>60%) within a specific potential range, and the highest CH4 Faradaic efficiency reaches 66.4%. The Faradaic efficiency of the byproducts H2 and CO is extremely low, with the optimal potential of H2<10% and CO<2%.
[0113] Combined with Example 9, it can be seen that although the mesoporous channels of MSN in the copper-based catalyst Cu-MSN-II are filled, the newly generated micropores can still improve the efficiency of catalysis. It is well known that porous materials have a highly ordered pore structure, which not only increases the specific surface area of the material, but also provides more exposure opportunities for the active sites of the catalyst. Specifically, with regard to the copper-based catalysts Cu-MSN-I and Cu-MSN-II prepared in this application, on the one hand, the high surface area means that more active sites can contact with the reactants, thereby improving the catalytic efficiency; on the other hand, the highly ordered pore structure allows the reactants to quickly enter the pores to reach the active sites, and the products can also be quickly discharged from the pores, avoiding the influence of diffusion limitation on the reaction rate. In addition, the microenvironment inside the pores may also have a protective effect on the catalyst surface, slowing down the poisoning and sintering process.
[0114] (2) In situ ATR-FTIR spectroscopy
[0115] Test method: The spectrometer (Thermo Fisher NicoletIS 50) equipped with a mercury cadmium telluride (MCT / B) detector and a VeeMAX III ATR accessory (Pike Technologies) were used to obtain the data. A three-electrode spectroelectrochemical cell (Jackfish) was used as the electrolysis cell. The catalyst drop was cast on a sputtered gold silicon prism as the working electrode, and a standard Ag / AgCl electrode and a platinum wire were used as the reference electrode and the counter electrode. The electrolyte used was a 0.1M CO2-saturated KHCO3 solution. The electrochemical cell was connected to an electrochemical station and electrolysis was performed at a constant potential from 0V to -2.4V relative to RHE.
[0116] Test results: The copper-based catalyst Cu-MSN-I prepared in Example 2 and the copper-based catalyst Cu-MSN-II prepared in Example 5 are used as examples for illustration.
[0117] Fig.12 This is the in-situ infrared spectrum of the copper-based catalyst Cu-MSN-I. Fig.12 It can be seen that 2063cm -1 The peak at is attributed to the linear (CO L )C≡O stretching, and at higher reduction potentials, the *CO peak has a higher peak intensity. -1 The fluctuation at 2860cm indicates the possible presence of *CHO intermediates, which are important precursors for CH4 production. -1 and 2930cm -1 The fluctuations at *CH x The symmetric and asymmetric stretching vibrations of the groups indicate that there may be a continuous hydrogenation process during the conversion of the *CHO intermediate to CH4.-1 A weak *COH intermediate signal was observed at 1230 cm -1 and 1067cm -1 No significant carbon-carbon coupling intermediate signal was observed, indicating that Cu-MSN-I containing abundant Cu-O-Si sites tends to stabilize the hydrogenation of *CHO to CH4.
[0118] Fig.13 This is the in-situ infrared spectrum of the copper-based catalyst Cu-MSN-II. Fig.13 As shown, at 1391cm -1 The strong fluctuations at 1010, 1067 and 1230 cm indicate the possible existence of *COOH intermediates, while the spectrum of the copper-based catalyst Cu-MSN-I shows no *COOH intermediates. -1 The peaks at are attributed to *COH, *COCOH, and *OCCOH, respectively. The presence of two key intermediates of carbon-carbon coupling, *COCOH and *OCCOH, indicates that the copper-based catalyst Cu-MSN-II containing abundant Cu-O-Cu sites is beneficial to the coupling of *CO and *COH adsorbed on the adjacent Cu surface, thereby improving the selectivity of C2H4 generation.
[0119] Figure 15 is a graph of the Faraday efficiency of electrocatalytic CO2 reduction of smooth surface spherical nanospheres supported by copper catalysts prepared in Comparative Example 1-2. As shown in Figure 15, it can be seen that the Faraday efficiency of electrocatalytic CO2 reduction to the target product of the copper-based catalyst prepared in Comparative Example 1-2 is extremely low, and the current density is small, and the Faraday efficiency of the byproducts H2 and CO is very high, indicating that the catalyst does not have the potential to be an efficient electrocatalyst. It can be seen that only by using non-conductive silica nanospheres with semi-open pores as carriers, can copper-based catalysts have the potential to show excellent performance.
[0120] FIG. 16 is a graph showing the Faraday efficiency of electrocatalytic CO2 reduction of Cu-MSN catalysts with different Cu loadings prepared in Comparative Examples 3-5. Fig.16a It can be seen that the Faraday efficiency of the catalyst prepared in Comparative Example 3 for electrocatalytic reduction of CO2 to CH4 is lower, and it is obvious that the loading amount is not the optimal loading amount. Fig.16b It can be seen that the Faraday efficiency of the catalyst prepared in Comparative Example 4 for electrocatalytic reduction of CO2 to C2H4 and CH4 is lower than that of Cu-MSN-Ⅰ and Cu-MSN-Ⅱ, and it is obvious that the loading amount is not the optimal loading amount. Fig.16cIt can be seen that the Faraday efficiency of the catalyst prepared in Example 5 for electrocatalytic reduction of CO2 to C2H4 is lower than that of Cu-MSN-Ⅱ, and it is obvious that the loading amount is not the optimal loading amount. It can be seen that even if non-conductive silica nanospheres with semi-open pores are used as carriers, only when the copper-based catalyst loading amount is specific can the electrocatalytic reduction of carbon dioxide to produce methane show extremely high selectivity (FE of CH4>60%) and yield (Faraday efficiency of CH4 reaches 71.1%).
[0121] In summary, (1) the copper-based catalyst supported by silica nanospheres described in the present application pioneered the use of non-conductive silica nanospheres as carriers, and under a certain copper salt content, it showed excellent performance and produced unexpected technical effects - it showed extremely high selectivity (FE of CH4>60%) and yield (CH4 Faraday efficiency of 71.1%) in the electrocatalytic reduction of carbon dioxide to produce methane. (2) The copper-based catalyst supported by silica nanospheres described in the present invention not only has simple preparation steps and mild conditions, which is of great significance for practical applications, but also can freely achieve the regulation of the electrocatalytic carbon dioxide reduction product - methane or ethylene - by regulating the content of copper salt loaded in the MSN carrier, which can meet different needs and has a broader application prospect.
Claims
1. A method for preparing a copper-based catalyst for electrocatalytic reduction of CO2 to produce CH4, characterized in that: The following steps are involved: (1) Preparation of silica nanospheres: adding appropriate amounts of water, butyraldehyde and CTAB into a closed reaction device and stirring under alkaline conditions until the mixture is uniform; then adding appropriate amounts of TEOS and reacting at room temperature under stirring for 20-28 hours; liquid-solid separation, washing, drying and calcining the solid to obtain silica nanospheres with semi-open pore morphology, i.e., MSN carriers; wherein the mass ratio of water, butyraldehyde, CTAB and TEOS is 100-140:104-136:5-8:20-22; (2) Loading of copper-based catalyst: Take appropriate amount of MSN carrier prepared in step (1) and divalent copper salt in water, stir until the copper salt is dissolved and evenly dispersed; then add urea, stir and react at 60-100° C. under alkaline conditions for 3-5 hours; separate the liquid and solid, wash, dry and calcine the solid to obtain silica nanosphere-loaded copper-based catalyst Cu-MSN-I; wherein the amount of divalent copper salt is 1.4-1.6 mmol copper salt / g MSN carrier, and the amount of urea is 11-13 mmol urea / g MSN carrier.
2. The preparation method according to claim 1, characterized in that: The alkaline condition in step (1) is: pH=11-12; the alkaline condition in step (2) is: pH=10-11.
3. The preparation method according to claim 2, characterized in that: The divalent copper salt is copper chloride, copper nitrate or copper sulfate.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The washing in step (1) is specifically: washing with water or ethanol for 3-5 times; the drying is specifically: drying at 70-90° C. for 12-18 hours; The calcination is specifically as follows: heating to 500-550° C. at a heating rate of 10° C. / min, and calcining for 5-7 hours.
5. The preparation method according to any one of claims 1 to 3, characterized in that: The washing in step (2) is specifically: washing with water 3-5 times; the drying is specifically: drying at 50-70°C for 12-18 hours; the calcining is specifically: heating to 300-350°C at a heating rate of 10°C / min and calcining for 4h-6h.
6. The catalyst Cu-MSN-I prepared by the method according to any one of claims 1 to 5.
7. Use of the catalyst Cu-MSN-I as claimed in claim 6 in electrocatalytic CO2 reduction to produce CH4.
8. A method for preparing a copper-based catalyst for electrocatalytic reduction of CO2 to produce C2H4, characterized in that: The preparation method according to any one of claims 1 to 5 is adopted, wherein the amount of the divalent copper salt used in step (2) is 7 to 8 mmol copper salt / g MSN carrier; and a silica nanosphere-supported copper-based catalyst Cu-MSN-II is obtained.
9. The catalyst Cu-MSN-II prepared by the method of claim 8.
10. Use of the catalyst Cu-MSN-II as claimed in claim 9 in electrocatalytic reduction of CO2 to produce C2H4.
Citation Information
Patent Citations
Preparation method of copper nanosheet applied to efficient carbon dioxide reduction reaction to generate methane
CN112501662A
Dendritic ordered mesoporous copper oxide nano material, and preparation method and application thereof
CN113620334A
Preparation method of electro-catalysis electrode for preparing ethylene through electrochemical reduction of carbon dioxide
CN114381747A
Hierarchical porous material as well as preparation method and application thereof
CN114892196A
Core-shell material as well as preparation method and application thereof
CN116949493A